Long‐term nitrogen isotope dynamics in Encelia farinosa reflect plant demographics and climate. Issue 3 (24th August 2021) - Driscoll, Avery W.; Kannenberg, Steven A.; Ehleringer, James R.
Summary: While plant δ 15 N values have been applied to understand nitrogen (N) dynamics, uncertainties regarding intraspecific and temporal variability currently limit their application. We used a 28 yr record of δ 15 N values from two Mojave Desert populations of Encelia farinosa to clarify sources of population‐level variability. We leveraged > 3500 foliar δ 15 N observations collected alongside structural, physiological, and climatic data to identify plant and environmental contributors to δ 15 N values. Additional sampling of soils, roots, stems, and leaves enabled assessment of the distribution of soil N content and δ 15 N, intra‐plant fractionations, and relationships between soil and plant δ 15 N values. We observed extensive within‐population variability in foliar δ 15 N values and found plant age and foliar %N to be the strongest predictors of individual δ 15 N values. There were consistent differences between root, stem, and leaf δ 15 N values (spanning c . 3‰), but plant and bulk soil δ 15 N values were unrelated. Plant‐level variables played a strong role in influencing foliar δ 15 N values, and interannual relationships between climate and δ 15 N values were counter to previously recognized spatial patterns. This long‐term record provides insights regarding the interpretation of δ 15 N values that were not available from previous large‐scale syntheses, broadly enabling more effective application of foliar δ 15 N values.